Strategi Komunikasi Pemberdayaan Ekonomi Perempuan Madura Berbasis Kearifan Lokal Madura - Farida Nurul Rahmawati; Nikmah Suryandari; Netty Dyah Kurniasari (Jurusan Ilmu Komunikasi UTM, 2013)
The life cycle of Madurese women is full of local wisdom, which can be the basis of the improvement of their economic welfare if it is well developed. Yet, the Madurese women are not aware of this potential. Hence, the objective of this research is to design a local wisdom based strategy to empower the economy of Madurese women. The communication strategy is in the form of a model which is validated by Madurese women. From the implementation of the model, then, the Madurese women entrepreneur which is based on local wisdom is formedThis research which was conducted in Sampang regency applied descriptive qualitative analysis. This research employed some methods, specifically (1) documentation analysis of the result of the first research to design the strategy of madurese women empowerment, (2) FGD, (3) action research to validate the strategy, (4) observation, and (5) deep interview to accomplish the model of Madurese women empowerment strategyFrom the data analysis the communication strategy is then designed as follows: (1) the communicator is the successful businesman, TKB, and the entrepreneur,' (2) the message is the entrepreneurship training with direct practice as well as the training of how to create creative industrial product which matches the local potential; (3) the media is props and slide; (4) the communicant is the member of kopwan. The communication strategy done by the components of the communication above is as follow.. the communicator visits the communicants and does an informal approach to give an entrepreneur training in the field of industrial creativity which is based on the local potential. The feedback may be gained directly and the face-to-face meeting is carried out as informal as possible without classical format. Then, the products as the result of their works are marketed directly to the Sara, i.e. by visiting crowded places like traditional market or by conducting